Effect of Tax Understanding, Tax Sanctions, and Tax Rates on Tax Compliance With MSMEs - Azahra, Jasmine Afianda; Trisnaningsih, Sri (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose : This study analyzes the effect of tax understanding, tax sanctions, and tax rates on tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Gunung Anyar District, Indonesia. Methodology: A quantitative method was employed using a structured questionnaire distributed to 51 MSME actors. Multiple linear regression was conducted using SPSS 25. Findings: Tax understanding and tax sanctions have a positive significant effect on MSME tax compliance. Conversely, tax rates have a significant negative effect. Results: The model explains 52.7% of the variation in tax compliance (R² = 0.527). All classical assumptions (normality, multicollinearity, autocorrelation, heteroscedasticity) were met. Novelty: This research highlights compliance issues in the growing MSME sector post-implementation of reduced tax rates. Originality: The study integrates Theory of Planned Behavior into a taxation compliance context among MSMEs. Conclusions: Higher tax knowledge and sanctions improve compliance, while perceived tax burden diminishes it. Type of Paper: Empirical quantitative research.